ANALISIS PENETAPAN HARGA POKOK PRODUKSI PADA PT BARATA INDONESIA (PERSERO) - Dwi Nazilah Octaviyah; Anik Yuliati (Fakultas Ekonomi Universitas Islam Darul Ulum Lamongan, 2024)
The cost of production has an important role in the company's decision-making process such as determining the selling price and evaluation. Each company certainly has its own way of determining the COGS for the products it produces. This study aims to determine and explain the methods used by PT Barata Indonesia (Persero) in determining the cost of goods manufactured, as well as to determine the grouping of costs used in the calculation of cost of goods manufactured. This research was conducted using a descriptive qualitative approach. The results showed that PT Barata Indonesia (Persero) calculated COGS using the full costing method and collected costs using the job order costing method. There are differences in COGS calculation format and cost grouping. At PT Barata Indonesia (Persero), overheat costs are divided into machine costs, other overhead costs, subcontract costs, and BPTL, while in theory there is only one overhead cost group. The difference in cost grouping is in the grouping of auxiliary material costs and the grouping of transportation or shipping costs.